Effect of Noble Metal Thin Film Thicknesses on Surface Plasmon Resonance (SPR) Signal Amplification - Wan Maisarah Mukhtar; Nursyamimi Raidah Ayob; Razman Mohd Halim; Nurul Diyanah Samsuri; Noor Faezah Murat; Karsono Ahmad Dasuki; Affa Rozana Abdul Rashid (Penerbit Akademia Baru, 2024)
Non-Indexed Publication